An overview of SARS-CoV-2 viral proteins with relevance to improved diagnostic and therapeutic platforms - Chung, Christopher; Irudayaraj, Pratiba; Lallow, Emran; Xu, Ziyang; Park, Young K.; Kudchodkar, Sagar B.; Montaner, Luis J.; Srinivasan, Alagarsamy; Muthumani, Kar (Frontiers in Virology, 2024)
In the past 25 years, the world has witnessed outbreaks of illnesses in humans from three different coronaviruses. Both the SARS-CoV outbreak of 2003 and the MERS-CoV outbreak of 2013 resulted in overall low fatalities in part due to inefficient human-to-human spread of each virus. In contrast, SARS-CoV-2, which emerged in 2019, was highly efficient at human-to-human spread and caused a global pandemic resulting in millions of casualties. Zoonotic transmission of viruses, including the three coronaviruses, poses an ongoing threat that cannot be ignored. In this review, we have focused on the diagnostics and therapeutics fronts using SARS-CoV-2 as a model. Specifically, we have selected proteins associated with the virus particles as targets and discussed various platform technologies. These insights hold the potential to inform the development of more effective therapeutics and vaccines not only for SARS-CoV-2 but also for future viral pandemics, thus contributing to global health on a broader scale.